2005
DOI: 10.1021/jf050702d
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of (+)- and (−)-Gossypol in Wild Species of Cotton and in Gossypium hirsutum Var. marie-galante (Watt) Hutchinson

Abstract: Gossypol occurs as a mixture of enantiomers in cottonseed. These enantiomers exhibit different biological activities. The (-)-enantiomer is toxic to animals, but it has potential medicinal uses. Therefore, cottonseed with >95% (-)-gossypol could have biopharmaceutical applications. The (+)-enantiomer shows little, if any, toxicity to nonruminant animals. Thus, cottonseed with >95% (+)-gossypol could be more readily utilized as a feed for nonruminants. The (+)- to (-)-gossypol ratio in commercial Upland (Gossyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 16 publications
1
55
0
Order By: Relevance
“…One such example is the study of gossypol (+) and (-) enantiomers, found in the cotton plant. These enantiomers have been shown to differ in toxicity to herbivores and pathogens (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…One such example is the study of gossypol (+) and (-) enantiomers, found in the cotton plant. These enantiomers have been shown to differ in toxicity to herbivores and pathogens (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Among G. hirsutum entriesin the 2012 National Cotton Variety Test, percent total gossypol ranged from 0.55% to 1.89% (www.ars.usda.gov/SP2UserFiles/Place/64021500/2012NCVT.pdf). Gossypol exists as enantiomers (isomers) referred to as (+)-and (−)-gossypol [5] [6] with the (−) enantiomer reported to be more toxic than the (+)-enantiomer. For example, the (−)-enantiomer exhibited a greater ability to inhibit the growth of cancer cell lines [7] [8].…”
Section: Introductionmentioning
confidence: 99%
“…(+)-gossypol is the dominant form, which could make up to 97% in G. hirsutum var. mariegalante (Stipanovic et al, 2005). Moreover, the content and ratio also vary in tissues.…”
Section: Sesquiterpenoids In Cottonmentioning
confidence: 99%
“…in G. hirsutum var. mariegalante, the (+)-gossypol accounts for about 98% (Stipanovic et al, 2005). In plants, a family of dirigent proteins plays a key role in determining the stereo specificity.…”
Section: Peroxidase Laccase and Dirigent Proteinmentioning
confidence: 99%